2021
DOI: 10.1002/cbic.202100577
|View full text |Cite|
|
Sign up to set email alerts
|

Scalable and Selective β‐Hydroxy‐α‐Amino Acid Synthesis Catalyzed by Promiscuous l‐Threonine Transaldolase ObiH

Abstract: Enzymes from secondary metabolic pathways possess broad potential for the selective synthesis of complex bioactive molecules. However, the practical application of these enzymes for organic synthesis is dependent on the development of efficient, economical, operationally simple, and well-characterized systems for preparative scale reactions. We sought to bridge this knowledge gap for the selective biocatalytic synthesis of β-hydroxy-α-amino acids, which are important synthetic building blocks. To achieve this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 67 publications
(88 reference statements)
1
26
0
Order By: Relevance
“…Naphthyl-2-aldehyde was previously observed to react with ObiH. 14 Here, we observed that the naphthyl-1-epoxide 15a reacted in the cascade to produce the corresponding amino acid 15b with a 25% yield. To assess whether SOI could convert epoxide functionalized aromatic heterocycles into the corresponding α-aryl aldehyde, we synthesized oxiranyl pyridine substrates from 2-, 3-, and 4-pyridine carboxaldehydes.…”
Section: Co-expression Of Soi and Obihmentioning
confidence: 55%
See 3 more Smart Citations
“…Naphthyl-2-aldehyde was previously observed to react with ObiH. 14 Here, we observed that the naphthyl-1-epoxide 15a reacted in the cascade to produce the corresponding amino acid 15b with a 25% yield. To assess whether SOI could convert epoxide functionalized aromatic heterocycles into the corresponding α-aryl aldehyde, we synthesized oxiranyl pyridine substrates from 2-, 3-, and 4-pyridine carboxaldehydes.…”
Section: Co-expression Of Soi and Obihmentioning
confidence: 55%
“…Previous studies by us and others have shown that ObiH has excellent stereoselectivity. 14,31,32 The S-isomer at the 2position (C α ) is formed due to the complete facial selectivity of the ObiH quinonoid nucleophile. ObiH forms the 3-(R)isomer with high, >20:1 selectivity under initial velocity conditions for most substrates tested, which matches the absolute configuration of obafluorin, the natural product produced in the biosynthetic pathway encoding ObiH.…”
Section: Co-expression Of Soi and Obihmentioning
confidence: 99%
See 2 more Smart Citations
“…While there are excellent synthetic methods to access many nsAAs, [8–10] biocatalytic routes offer distinct advantages. Enzymes operate under mild conditions with no protecting groups and can be combined in cascades to build complex molecules from simple precursors in a regio‐ and stereoselective fashion [11–13] . Identifying and characterizing new classes of enzymes that can meet the demands of preparative‐scale synthesis will provide additional tools for the facile synthesis of desirable nsAAs.…”
Section: Introductionmentioning
confidence: 99%